2010
DOI: 10.1016/j.jallcom.2009.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogen content on hot deformation behavior and microstructural evolution of Ti600 alloy

Abstract: Isothermal hot compression tests of a Ti600 alloy after hydrogenation were carried out over the temperature range of 760 to 880℃ and strain rate range of 0.01 to 10 s-1. The influence of hydrogen content was studied on the flow stress and activation energy of deformation. The microstructural changes were examined by transmission electron microscopy (TEM). The results show that the addition of 0.3% hydrogen in Ti600 alloy can decrease the hot deformation temperature by 80 •C and increase the deformation strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The spheroidization of secondary α phase is more obvious. Furthermore, as the strain rate increases, the proportion of β t increases with strain rate, which is ascribed to the adiabatic temperature rising caused by the low thermal conductivity of titanium during the high strain rate deformation [33]. TEM micrographs are shown in Figure 10 to investigate the effect of the strain rate on the evolution of matrix microstructure.…”
Section: Effect Of Deformation Temperaturementioning
confidence: 99%
“…The spheroidization of secondary α phase is more obvious. Furthermore, as the strain rate increases, the proportion of β t increases with strain rate, which is ascribed to the adiabatic temperature rising caused by the low thermal conductivity of titanium during the high strain rate deformation [33]. TEM micrographs are shown in Figure 10 to investigate the effect of the strain rate on the evolution of matrix microstructure.…”
Section: Effect Of Deformation Temperaturementioning
confidence: 99%
“…The Zener-Hollomon parameter, as a temperature compensated strain rate factor, can be used to describe the combined effects of temperature and strain rate on the hot deformation process [26,27]. The expression of material's hot deformation behavior represented by the Z parameter is obtained as: Table 4.…”
Section: Constitutive Analysis Of Experiments Alloymentioning
confidence: 99%
“…In refs. [84][85][86][87], the effect of THP on the hot working of Ti600 (Ti-6Al-2.8Sn-4Zr-0.5Mo-0.4Si-0.1Y) was investigated. It was found that the flow stress could be greatly reduced within hydrogen content range of 0.1-0.3wt%.…”
Section: Improvement Of Microstructure Mechanical Properties and Wormentioning
confidence: 99%